A2.3 Management of children with congenital nephrotic syndrome: challenging treatment paradigms. (4th October 2017) - Dufek, S; Shroff, R; Ylinen, E; Trautmann, A; Alpay, H; Ariceta, G; Aufricht, C; Bacchetta, J; Bakkaloglu, S; Bayazit, A; Cicek, RY; Dursun, I; et al.
Abstract : Background: Management of children with congenital nephrotic syndrome (CNS) is challenging. Early bilateral nephrectomies followed by dialysis and transplantation is currently practised in most centres, but conservative treatment may also be effective. Methods: We conducted a 6 year survey across members of the European Society for Paediatric Nephrology Dialysis Working Group to compare management strategies and their outcomes in children with CNS. Results: 81 children (51% male) across 17 tertiary nephrology units in Europe were included (NPHS1 n=57; NPHS n=2, WT1 n=10, others n=12; details of mutations not examined). Antiproteinuric treatment was given in 48 (59%) with an increase in S-albumin in 68% by median 6 (interquartile range 3–8) g/L (p<0.001). Unilateral nephrectomy (or first kidney removal) was performed in 16 children. In those, S-albumin increased by 3 (1–7) g/L (p=0.021) and weekly albumin infusion dose decreased by 4 (0–7) g/kg/week (p=0.018). The median age at bilateral nephrectomy was 9 months. Dialysis was initiated in 53 (65%) at a median age of 9 (5.5–15) months, with PD in 91% of children. Children with NPHS1 mutations and >12 months follow-up were divided into two groups and their outcomes were compared: bilateral nephrectomy (n=26) versus conservative management (no nephrectomy; n=17). Nephrectomised children presented earlier (3 vs 29 days; p=0.01), with comparable S-albumin (p=0.21) and S-creatinine (p=0.19). There was no difference in the number of septic or thrombotic episodes and growth was comparable. At final follow-up (median age 34 months) 9 (53%) children in the conservative group remained without renal replacement therapy, 4 (24%) received a renal transplant and 2 died. Amongst nephrectomised children 21 (81%; p<0.01) were transplanted and 1 died. Conclusion: An individualised, stepwise approach, with prolonged conservative management, followed by unilateral nephrectomy may be a reasonable alternative to early bilateral nephrectomies in children with CNS secondary to NPHS1 mutations.